Edukasi budidaya jamur tiram (Pleurotus ostreatus) di Madrasah Aliyah Negeri (MAN) 1 Polewali Mandar - Iqraini D., Nurul; Alfiani, St Hijrah; Ramlah, Ramlah (Agriculture and Forestry Faculty, Universitas Sulawesi Barat, 2024)
This community service aims to educate students of Madrasah Aliyah Negeri (MAN) 1 Polewali Mandar about the potential of oyster mushroom cultivation (Pleurotus ostreatus) as an effort to improve vocational understanding and entrepreneurial spirit. This activity is motivated by the high economic potential of oyster mushrooms and the need to diversify students' learning to face future challenges. The implementation method is by presenting educational materials related to oyster mushroom cultivation. This activity took place in March-June 2024, involving 50 grade XI students. The material provided includes an introduction to oyster mushrooms, nutritional content, cultivation techniques, challenges, and opportunities for the economic benefits of oyster mushroom cultivation. 84% of participants gave a positive response (Yes), and 16% gave a negative response (No) to all aspects evaluated. This shows that the oyster mushroom cultivation education activity has succeeded in significantly increasing participants' knowledge, interest, and motivation, as well as providing benefits according to the needs of the participants. The main challenges faced include limited resources. However, effective collaboration with the school helped overcome these obstacles. This activity not only succeeded in transferring knowledge and understanding but also stimulated students' interest in entrepreneurship in agriculture. The program's sustainability is guaranteed through integrating materials into the school curriculum and the development plan for oyster mushroom production units in the madrasah environment. This service concludes that oyster mushroom cultivation education has great potential in preparing madrasah students to face economic opportunities in agribusiness.